Survey of vulnerable Amazonian manatees using environmental DNA (eDNA): A method for survey in remote field settings - Kaitlyn Romoser; Shizuka Hashimoto; Nasrah M. C. Hamdan; Leonardo Sena; Miriam Marmontel; Tomas Hrbek; Izeni P. Farias; Kirk O. Winemiller (PLoS ONE, 2026)
The only exclusively freshwater lineage of Sirenia, the Amazonian manatee (Trichechus inunguis ) is listed by the IUCN as vulnerable, with populations projected to decline further during the coming decades. Given that illegal hunting, pollution, habitat disturbance and other impacts are ongoing, it is imperative to assess the distribution and abundance of this unique, elusive aquatic mammal. In this study, we used environmental DNA (eDNA) methods to test for T. inunguis presence at three locations along the longitudinal gradient of the Amazon River and its tributaries (Tefé, Manaus, Belém). At each location, water samples were collected at sites spanning a disturbance gradient from urban to protected reserves. We developed a field methodology to preserve DNA for up to 13 days or more without requiring freezing or cooling of samples. This method performed similarly to traditional cold-storage methods used for eDNA research. In the lab, DNA was extracted from the samples followed by PCR amplification, and Illumina sequencing. Detection of Amazonian manatee DNA was more than three times greater in the western Amazon (Tefé and Mamirauá Reserve) where human activity is low. Manatee DNA was detected at six sites in the central Amazon (Manaus) and in only two sites in the eastern Amazon near the coast (Belém) where human populations and impacts are greater. eDNA methodology was effective for detecting manatees and is expected to be useful for estimating their broader distribution as well as surveying other aquatic species in tropical rivers.